Mind the gap: Coping with delay in environmental governance - Karlsson, Mikael (Ambio, 2019)
Gaps between public policy goals and the state of the environment are often significant. However, while goal failures in environmental governance are studied in a number of disciplines, the knowledge on the various causes behind delayed goal achievement is still incomplete. In this article we propose a new framework for analysis of delay mechanisms in science and policy, with the intention to provide a complementary lens for describing, analysing and counteracting delay in environmental governance. The framework is based on case-study findings from recent research focusing on goal-failures in policies for climate change, hazardous chemicals, biodiversity loss and eutrophication. It is also related to previous research on science and policy processes and their interactions. We exemplify the framework with two delay mechanisms that we consider particularly important to highlight—denial of science and decision thresholds. We call for further research in the field, for development of the framework, and not least for increased attention to delay mechanisms in environmental policy review and development on national as well as international levels.